Pile Capacity Behavior of Very Long Bored Piles in Bangkok Soil - Aunmongkonmit, Siam; Boonyarak, Thayanan; Zaw Zaw Aye (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
Urbanization in Bangkok necessitates large-scale construction that often conflicts with the city's limited space. To address this challenge, very long bored piles (exceeding 60 meters) have emerged as a more suitable geotechnical solution for supporting high-rise buildings, deep excavations, and large infrastructure projects. These piles offer potential benefits such as reduced construction time, lower costs, and a smaller carbon footprint. This study investigates the effects of pile length, diameter, and ultimate bearing capacity by analyzing monitoring data from numerous projects in Bangkok, focusing on factors such as skin friction, and end-bearing resistance. Static pile load test results for piles ranging from 60 to 100 meters in length demonstrate that extended pile lengths significantly enhance load capacity, primarily due to increased shaft friction at greater depths, represented by higher friction factors (b). These findings suggest that longer piles can replace or reduce the number of conventional bored piles, resulting in a 50% increase in load capacity per unit volume of concrete. This also leads to a reduction in total concrete consumption. Additionally, while traditional pile designs required a safety factor of 2.5, static pile load tests allow for a reduced safety factor of 2.0, potentially cutting the carbon footprint by 25%. Moreover, the substitution of bentonite slurry with polymer slurry further improves the ultimate bearing capacity and settlement performance of bored piles, making them more efficient and sustainable for urban geotechnical applications. piles.